2018
DOI: 10.1108/ijlss-09-2016-0047
|View full text |Cite
|
Sign up to set email alerts
|

Lean Six Sigma in developing countries: evidence from a large Brazilian manufacturing firm

Abstract: Purpose Although the literature on Lean Six Sigma (LSS) implementation has evolved, a deeper understanding of the LSS practices applied in organisations in developing countries is needed. This paper aims to analyse LSS in a manufacturing company in the context of LSS implementation in an emerging economy. Design/methodology/approach This paper uses case-based research. Data collected in a large manufacturing company through multiple sources of evidence were triangulated to derive the findings. This paper ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 53 publications
(121 reference statements)
1
18
0
1
Order By: Relevance
“…Nevertheless, the integration of Lean and Six Sigma approach has appeared to be challenging (Habidin et al , 2016; Muraliraj et al , 2018; Moya et al , 2019; Alblooshi et al , 2020). Previous studies suggested that the lack of awareness training, top management commitment and resistance to change were the common challenges of LSS deployment (Albliwi et al , 2015; Scheller et al , 2018; Moya et al , 2019; Alblooshi et al , 2020; Sony et al , 2020). Hence, it is inevitably crucial for top management to provide trainings and equip employees with necessary skills and knowledge to overcome their resistance to change and to ensure the successful implementation of LSS (Antony et al , 2017; Sony et al , 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, the integration of Lean and Six Sigma approach has appeared to be challenging (Habidin et al , 2016; Muraliraj et al , 2018; Moya et al , 2019; Alblooshi et al , 2020). Previous studies suggested that the lack of awareness training, top management commitment and resistance to change were the common challenges of LSS deployment (Albliwi et al , 2015; Scheller et al , 2018; Moya et al , 2019; Alblooshi et al , 2020; Sony et al , 2020). Hence, it is inevitably crucial for top management to provide trainings and equip employees with necessary skills and knowledge to overcome their resistance to change and to ensure the successful implementation of LSS (Antony et al , 2017; Sony et al , 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Lean organizations should embrace Six Sigma approach, making use of its data-driven decision-making tools and engage in a more scientific approach to quality improvement (Albliwi et al , 2015; Sunder, 2016). Lean and Six Sigma practices complement each other, overcoming individual shortfalls with Six Sigma focuses primarily on reducing variation, whilst Lean focuses on improving the flow in value stream and reduction of lead time which subsequently leads to quality improvement (Albliwi et al , 2015; Pacheco et al , 2015; Sunder, 2016; Swarnakar and Vinodh, 2016; Scheller et al , 2018; Moya et al , 2019; Muganyi et al , 2019; Walter and Paladini, 2019; Alblooshi et al , 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Lean transformation process entails top management investing in the development of work-related knowledge and skills (Caroline et al, 2016). Training empowers and motivates employees to participate in Lean implementation (Kappelman and Prybutok, 1995;Sorooshian and Mad Ali, 2017;Belhadi et al, 2019;Scheller et al, 2018). Employee training is also a prerequisite for the meaningful decentralization of decision rights to individual employees and teams (Caroline et al, 2016;Njie et al, 2008).…”
Section: Top Management Commitment and Leanmentioning
confidence: 99%
“…Meskipun six sigma telah diterapkan dengan sukses di banyak perusahaan besar, masih ada bukti yang kurang terdokumentasi tentang penerapannya di organisasi yang lebih kecil (Jiju et.all, 2005). Penelitian tentang penerapan six sigma di perusahaan kecil menengah diantaranya dilakukan oleh Kandil dan Aziz (2017), Scheller et al, (2017), dan Swarnakar, Tiwari dan Singh, (2020). Penulis Korespondensi: Telp : +62 878-2149-5772 e-mail : cucuwahyudin100@gmail.com Penelitian Kandil dan Aziz (2017) berfokus pada masalah yang terkait dengan rantai pasokan pada usaha kecil menengah di Mesir.…”
Section: Pendahuluanunclassified